Kualitas Pelayanan Publik Pada Balai Penunjang Pelayanan Kesehatan Provinsi Sulawesi Utara - Rembet, Debir Gilberto; Areros, William Agustinus; Goni, Sherly Y. V. I (JURNAL ILMIAH SOCIETY, 2015)
The work shown by the Center for Health Care Support will determine where the level of health and prevention on health problems faced and the other circumstances relating to the results - the results of laboratory tests. This study aimed to analyze the quality of service at the Center for Health Care Support North Sulawesi province in the development of management science of public administration.The conclusion of this study is the quality of service at the Center for Health Care Support North Sulawesi either do not fully seen from the dimensions of tangibles, reliability, responsiveness, assurance and empathy. Advised him to make improvements and additional work space and room service, adding laboratory test equipment adapted to existing testing activities, which include employee training specifically on the feasibility examination of laboratory equipment, placing employees who serve as customer service as well as receive complaints on service and foster the spirit of professional ethics to all employees through training component service excellen.Keywords: Quality, Health Services, Testing Laboratory.